Robust portfolio optimization of hybrid renewable energy system - Ahmadi, Afshin
Hybrid renewable energy systems (HRES) have received much attention over the past few years. A hybrid renewable system consists of two or more renewable energy sources, inverters, controller, interfaced generators, and generally an energy storage bank (e.g. batteries). Today, the costs between different renewable technologies are very close (e.g. site development, transmission line development, etc.) and power demand, the average cost of energy produced by each renewable source may vary from one case to another. In this study , a robust methodology is developed to determine the least cost combination of renewable technologies (e.g. wind, solar, Biomass and hydro) in a hybrid renewable system. For this purpose, simplified dynamic programming together with production simulation is used. The developed technology is capable of optimizing the renewable portfolio considering constraints such as availability of the renewable units in the market, regulations on maximum hourly production by all renewable units, restrictions on the number of renewable units, hourly demand, and availability of the renewable resources. A computer program has been developed to evaluate the methodology. Five scenarios with different annual peak demands are simulated and the results are provided. The simulation result suggests the optimal combination of renewable units.